Effect of plant lectins on larval development of legume pod borer, Maruca vitrata - Machuka, J.; Damme, E.V.; Peumans, W.J.; Jackai, L.E.N. (1999)
The legume pod‐borer Maruca vitrata (Fabricius), [Lepidoptera: Pyralidae] is a major constraint restricting increased cowpea production in tropical Africa and Asia. Since lectins are known to have insecticidal properties against several pests, a survey was undertaken to screen for the effects of 25 lectins from 15 plant families on the development of Maruca pod borer (MPB) larvae. The list included 8 galactose/N‐acetylgalactosamine‐, 7 mannose‐, 5 complex glycan‐, 2 sialic acid‐ and 3, N‐acetylglucosamine‐specific lectins. Feeding bioassays using artificial diet were carried out at 2% (w/w) topical levels. Although a total of 16 lectins had detrimental effects pertaining either to larval survival, weight, feeding inhibition, pupation, adult emergence and/or fecundity, only the Listera ovata agglutinin (LOA) (Orchidaceae) and Galanthus nivalis (Amaryllidaceae) agglutinin were effective against MPB larvae for all six parameters examined. Larval mortality and feeding inhibition caused by the most active lectin (LOA) was above 60%.